Music therapy and its effects in the hospital environment (Research, Society and Development, 2022)
Objective: To understand the importance of music as a practice present in the hospital environment and in nursing care Method: This is a literature review study on the effects of music therapy in the hospital environment. The search will be done through data contained in the Virtual Health Library (VHL). Where, through the advanced form of this base, the terms "Music Therapy", "nursing care" were used in the words field and "BRAZIL" in the Country field, year of publication 2008 - 2019. After a selection of these articles found, they were selected those that best contributed to the objective of the research, among them approaching the theme of the effects of music in the hospital routine and the connection of music in nursing care. Results: Based on the studies found, we can see that for some time now music has been used as a therapeutic, non-pharmacological form to relieve certain physical and mental symptoms in patients and employees within a health unit, thereby raising awareness of the care, generating a more humanized work. Therefore, with this analysis, we seek to list the impacts of music in different sectors of care, identify the effects of music therapy on patients, health professionals in the hospital environment, and thus emphasize the importance of this practice in nursing care. Final considerations: Bringing references from hundreds of years showing the use of music in different cultures as a therapeutic and humanization form, it shows the importance that should be given to research in the genre, understanding that the objective of humanized practices is to find effective treatments, less evasive and non-medicated.